The Influence of Social Media Facebook and Twitter on Student’s Rational Choices - Lestari, Linayati; Langgeng Ratnasari, Sri (International Journal of Psychosocial Rehabilitation, 2020)
The student rational choices contribute to elections. Student’s rational choices are one of the issues at the elections. The purpose of this study was to determine the influence of social media (Facebook and Twitter) on student’s rational choices. This type of research is a quantitative descriptive study with data collection techniques using a questionnaire. The study population was 1978 people with a sample of 322 students. The sampling technique uses the Krejcie & Morgan formula. Hypothesis Testing Results for Social Media Facebook Variables Significantly Influence Student’s Rational Choices. Hypothesis testing Social Media Twitter variables significantly influence Student’s Rational Choices. The results of hypothesis testing indicate that the Social Media Facebook and Twitter variables simultaneously have a significant influence on the Student’s Rational Choices. The study expected to serve as a reference to the electoral candidates in an effort to encourage the increasing number of electoral votes among universities